Retention Strategies PT. Coca-Cola Distribution Indonesia-Balinusa Dalam Meningkatkan Employee Engagement (Studi Kasus : Level Manajer) - Ni Wayan Putri Olga Wedanti; A.A.N. Eddy Supriyadinata Gorda (Jurnal Manajemen dan Bisnis, 2018)
ABSTRACTThe purpose of this study is to determine the perception of leader at the manager level of PT. Coca-Cola Distribution Indonesia-Balinusa against retention strategies implemented in improving employee engagement. Data collection techniques use observation, interview and documentation method. The data validity check is done by triangulation technique including triangulation of source and triangulation method and also combined with member check. The process of data analysis includes data collection, data reduction, data presentation and conclusion or data verification. There are eleven (11) strategies undertaken PT. Coca-Cola Distribution Indonesia-Balinusa in an effective employee retention program to increase employee engagement and prevent high-quality, high-performance talent or human resources from leaving the company. The strategies are (1) brand ambassador; (2) career opportunities; (3) leadership; (4) company values; (5) communication pattern; (6) employer brand; (7) employee empowerment; (8) my leader; (9) recognition; (10) safety; and (11) employee wellbeing.